Diagnosis of Pentacuspid Aortic Valve with Severe Regurgitation Using Three‐Dimensional Transesophageal Echocardiography. Issue 2 (24th September 2014) - Ozyilmaz, Sinem; Akgul, Ozgur; Guzeltas, Alper; Ozyilmaz, Isa
Mini‐Abstract We describe a 48‐year‐old female patient with a pentacuspid aortic valve and severe aortic regurgitation that was diagnosed using three‐dimensional transesophageal echocardiography.